(untitled) (Journal of Medical & Health Sciences Review, 2025)
Background: Healthcare workers in Public-Private Partnership (PPP)-operated hospitals in Bajaur Tribal District, Pakistan, face unique challenges due to the hybrid healthcare model, characterized by high stress levels, resource scarcity, and systemic barriers. Understanding the relationships between job stress, job satisfaction, and work performance in these settings is crucial for improving healthcare delivery and worker well-being. Objective: This study aimed to explore the lived experiences of healthcare workers in PPP hospitals, focusing on the impact of job stress on job satisfaction and work performance, and identifying the coping mechanisms that healthcare workers rely on to manage stress and sustain their performance in this challenging context. Methods: A qualitative phenomenological design was employed, utilizing Interpretative Phenomenological Analysis (IPA) to analyze data collected through semi-structured interviews with 20 healthcare workers, including doctors, nurses, paramedics, support staff, and administrative personnel. The data were transcribed verbatim, and thematic coding was conducted manually using Microsoft Word and Excel to identify emergent themes related to job stress, satisfaction, coping mechanisms, and performance. Results: The analysis revealed five key themes. Operational overload and stress emerged as a major source of strain, with healthcare workers facing high patient loads, resource shortages, and staff deficiencies, leading to significant stress and burnout. Additionally, systemic barriers in the PPP context, including delayed salaries, lack of specialists, and unclear administrative structures, exacerbated stress levels. Despite these challenges, job satisfaction acted as a buffer, with healthcare workers reporting fulfillment from helping patients, team support, and professional development. Coping mechanisms such as peer support, religious practices, and physical breaks were crucial in maintaining emotional and physical resilience. Finally, job stress negatively impacted work performance, causing delays in patient care, reduced focus, and errors. However, job satisfaction and effective coping strategies moderated these effects, helping healthcare workers maintain performance despite the stressors they faced. Conclusions: This study highlights the significant role of job satisfaction and coping mechanisms in mitigating the adverse effects of job stress on work performance in PPP hospitals. The systemic barriers and operational overload faced by healthcare workers in resource-scarce settings call for urgent policy interventions to address staffing shortages, improve resource allocation, and provide emotional and social support. Enhancing job satisfaction and support systems will be crucial in improving healthcare delivery and the well-being of healthcare workers in these environments.